Design of Virtual Lab Geometry Using Virtual to Supplement Learning In Mathematics Classes - Buchori, Achmad; Prasetyowati, Dina; ., Wijayanto (KnE Social Sciences, 2022)
In learning the geometry of the parallels, there is a misconception between the position of the two lines and the position of the two angles. One way by which students can learn this material better is by virtual reality-based virtual lab media that is able to display objects like in the real world. The purpose of this research is to design the learning media, Virtual Laboratory Geometry Based on Virtual Reality so that students of the mathematics education study program at the Universitas PGRI Semarang are able to understand the alignment material accurately. This study uses ADDIE model development research with five steps that are carried out systematically. Virtual reality-based geometry lab application products have been validated by learning materials experts and learning media experts with scores of 91 and 92, which are categorized as very suitable for use in learning geometry in the classroom. Keywords: Design; Virtual Geometry Lab; Supplements; Learning Media